Multicultural Competence Awarness among International Students in Yogyakarta State University - Romano Galindo, Edith; Andriyanti, Erna (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research aimed to describe and interpret the characteristics of multicultural awareness of seven international students studying tertiary education in the postgraduate studies department at Yogyakarta State University. When individuals moved to a place where more than one culture coexists, they were now part of a multicultural society. In this respect, one of the many reasons for the existence of multicultural societies was the student mobility phenomenon in which many students decided to live abroad to pursue their academic goals. Accordingly, these students faced new cultural situations, and there was no doubt that they needed to use their multicultural competencies. However, were they aware of their own multicultural competence? Had the way they conceptualized it ever helped them to achieve their professional goals? In the research, such questions highlighted the relevance of focusing on the existing knowledge about multicultural competence of international students, which might provide insights into the role of multicultural competence as an inherent aspect of life to achieve personal or professional goals and strengthen their intercultural communication. Many pieces of research have already focused on the teachers’ multicultural competence and the importance of incorporating it in the programs. However, not many of them focused on the way students conceptualized it and perceived it in their lives. By using qualitative research and making use of a questionnaire as the main instrument, the findings show that students have a high level of awareness, and they mostly conceive it as a tool to achieve their professional goals.